2021
DOI: 10.3390/healthcare9080989
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Care and Self-Management among Patients with Stroke: A Cross-Sectional Study

Abstract: (1) Background: Stroke is an important topic in the healthcare industry. The objective of the present study was to investigate patients’ sociodemographic characteristics, health status, continuity of care, self-management, and other predictors that affect their self-management. (2) Methods: This cross-sectional correlational study was carried out from March to September 2020, and included a total of 150 patients aged 20 and above who were diagnosed within the past 6 months. The research participants were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…Nevertheless, no significant association was observed between gender and self-management behavior. The results of this study align with those of Kuo et al (2021) who indicated a lack of correlation between gender and the variables investigated in this study. The ability of both male and female patients to modify their self-management behavior is contingent upon their goals and self-efficacy.…”
Section: Correlation Between Individual-related Factors and Self-mana...supporting
confidence: 90%
“…Nevertheless, no significant association was observed between gender and self-management behavior. The results of this study align with those of Kuo et al (2021) who indicated a lack of correlation between gender and the variables investigated in this study. The ability of both male and female patients to modify their self-management behavior is contingent upon their goals and self-efficacy.…”
Section: Correlation Between Individual-related Factors and Self-mana...supporting
confidence: 90%
“…The process of health empowerment helps patients to take an active role in managing their own health, increasing their sense of control over their lives, ensuring continuity of care, and improving their self-confidence (Sit et al, 2016). Health professionals’ roles in delivering appropriate care and ensuring its continuity is crucial for supporting self-management in stroke patients (Kuo et al, 2021; Si et al, 2021). Optimizing stroke patients’ capacity to manage their own condition is of paramount importance (Lo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%